Integrated Use of Biostimulants, Biofertilizers, and Organic Waste Management for Sustainable Remediation of Degraded and Contaminated Soils: A Critical Review - Diksha Vishwakarma; Shashi S Yadav; Subhash Chandra Gupta (Public Health, 2026)
Soil degradation and contamination caused by industrialization, intensive agriculture, and improper waste disposal threaten global food security and ecosystem sustainability. Environmentally compatible approaches such as biostimulants, biofertilizers, and organic waste amendments have emerged as viable tools for restoring soil health and mitigating contaminants. This review synthesizes findings from recent original research to evaluate the effectiveness of these biological interventions in improving soil physicochemical properties, enhancing microbial activity, and facilitating pollutant immobilization or degradation. Biostimulants, including humic substances and seaweed extracts, improve plant resilience and nutrient uptake, while biofertilizers such as nitrogen-fixing and phosphate-solubilizing microorganisms contribute to nutrient cycling and soil fertility. Organic waste management practices, including composting and biochar application, play a critical role in reducing toxicity and enhancing carbon sequestration. The integration of these strategies demonstrates synergistic effects in remediating degraded soils and supporting sustainable agriculture. However, variability in field performance, lack of standardized application protocols, and limited long-term studies remain key challenges. Future research should focus on multi-functional formulations, microbial consortia optimization, and field-scale validation to ensure practical applicability. This review highlights the potential of biologically driven soil remediation strategies as cost-effective and eco-friendly alternatives to conventional methods.